2020
DOI: 10.1016/j.heliyon.2020.e04001
|View full text |Cite
|
Sign up to set email alerts
|

Agro-financing and food production in Nigeria

Abstract: This study examines how agro-financing impacts on food production in Nigeria supporting Goal 2 of the 2030 Sustainable Development Goals (SDGs) which aims to "end hunger, achieve food security, improve nutrition, and promote sustainable agriculture". The study covers the period 1981-2018 using annual data sourced from the World Development Indicators (WDI) of the World Bank, Central Bank of Nigeria (CBN) Statistical Bulletin. The Johansen and the Canonical Cointegration approaches are employed and findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…They also argued that increased assess to credit for farmers will enable them acquire improved imputs which will boost food production and accessibility thereby reducing the scourge of food insecurity. This view was supported by [18], they butress the fact that adequate funding of agricultural sector by ensuring hitch-free credit availment and provision of land for the sector will facilitate food security.…”
Section: Empirical Literaturementioning
confidence: 99%
“…They also argued that increased assess to credit for farmers will enable them acquire improved imputs which will boost food production and accessibility thereby reducing the scourge of food insecurity. This view was supported by [18], they butress the fact that adequate funding of agricultural sector by ensuring hitch-free credit availment and provision of land for the sector will facilitate food security.…”
Section: Empirical Literaturementioning
confidence: 99%
“…As opined by Olofin et al [7], many Nigerian farmers have been denied access to credit due to the weak institutional framework. In a similar way, Osabohien et al [8] carried out a study on accountability in agricultural governance and food security in Nigeria, applying the autoregressive distribution lag (ARDL) and found that effectiveness in governance will enhance agricultural performance, which in the long-run, contributes to food security in Nigeria.…”
Section: Review Of Literaturementioning
confidence: 99%
“…All these are efforts to control quality, promote local content, massive production and exportation, and encourage local farmers. However, the impact of these policies has remained inconclusive, primarily owing to the continuous challenges of weak governance and low ICT infrastructure, among others things [7,8]. Flowing from above argument, this study contributes to extant studies by examining the impact of: (a) governance on food security, (b) ICT adoption on food security, and (c) ICT adoption and governance interaction on food security, using the system GMM, which, to the best of the authors' knowledge, before now, has not been considered in the extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…Access to finance and technology, especially indigenous technology, is an important factor that increases productivity and enhances food security in developing countries (Tweheyo, 2018;Osabohien et al 2018;Chang, Chatterjee and Kim, 2014;Abdu-Raheem and Worth, 2011;Shiferaw, Hellin and Muricho, 2011;Kristjanson et al 2005). In the literature, access to finance has played a positive role in increasing the standard of living, self-confidence and also in the diversification of livelihood strategies and thus increasing their productivities and income (Osabohien, et al 2020;Onyiriuba, et. al., 2020;Dejene, 2019;Kopparthi and Kagabo, 2012;Anyiro andOraku, 2011 Bauchet et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Acquired funds could also be used to diversified farming operations, which tend to increase income base of farmers and consequently increase productivities and food security (Dejene, 2019;Tenaw and Islam, 2009). Sustained increase in farm productivities (consequently, food security) is enhanced, and farmers are able to smooth consumption if they have access to formal credit (Osabohien, et al 2020;Anyiro and Oraku, 2011). Amazingly, the agriculture sector, which is the major driver of food security, has received less access to finance in developing countries due to high credit risk (Chang, Chatterjee and Kim, 2014;Kopparthi and Kagabo, 2012).…”
Section: Introductionmentioning
confidence: 99%